Habilidades linguística, cognitiva, sociocultural e socioemocional no currículo paulista de língua inglesa para os anos iniciais do ensino fundamental: uma análise crítico-reflexiva à luz de dimensões do letramento - Buto, Marcia Yoshiko (Universidade Federal de São Carlos, 2025)
This research offers a critical analysis of the São Paulo State Curriculum for English Language Teaching in the Early Years of Elementary Education (CP-LIAI), understanding it not as a neutral document but as a political and discursive artifact. Based on a qualitative and interpretative approach within the field of Critical Applied Linguistics, the study examines how the skills proposed for the 4th and 5th grades articulate, or fail to articulate, linguistic, cognitive, sociocultural, and socioemotional dimensions of English language learning, in light of theories of critical literacy and multiliteracies. The analysis revealed that the CP-LIAI presents some progressive elements, such as the emphasis on orality and ludic engagement, but remains largely tied to prescriptive and technicist logic. Inclusive pedagogical intentions often coexist with formulations focused on memorization and the isolated reproduction of linguistic structures, contradicting the principles of a situated, ethical, and plural language education. The lack of child-centered listening in the construction of the curriculum further limits its transformative potential. The study also emphasizes the central role of the teacher: it is through critical reading, pedagogical mediation, and daily reinvention that the curriculum can be re-signified. However, this requires adequate working conditions and public policies that promote continuous and critical teacher education. The findings suggest the need to review and expand the CP-LIAI based on principles of social justice, inclusion, and recognition of children’s voices. The curriculum, as a space of dispute, must be reinterpreted as a site for listening, creation, and transformation. English language education in early schooling should recognize the child as an epistemic subject, a meaning-maker, and an active participant in real and meaningful discursive practices.
Linguistic, cognitive, sociocultural, and socioemotional skills in São Paulo english curriculum for the early years of elementary education: a critical-reflective analysis in light of literacy dimensions
Keywords: Habilidades curriculares; Curriculum skills; Currículo paulista; São Paulo curriculum; Língua inglesa; English language; Anos iniciais; Early years; Educação linguística; Language education; Letramento crítico; Critical literacy; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA; 4. Educação de Qualidade